2013
DOI: 10.1186/1748-717x-8-261
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects on carotid intima-media thickness after radiotherapy in patients with nasopharyngeal carcinoma

Abstract: BackgroundVascular abnormalities are the predominant histologic changes associated with radiation in nasopharyngeal carcinoma (NPC). This study examined if the duration after radiotherapy correlates with the progression of carotid intima-media thickness (IMT) and investigated its relationship with inflammatory markers.MethodsOne hundred and five NPC patients post-radiotherapy for more than one year and 25 healthy control subjects were examined by B-mode ultrasound for IMT measurement at the far wall of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
2
34
1
1
Order By: Relevance
“…In contrast, if patients do not have carotid plaque, the screening for carotid plaque may be performed in the fourth year after RT. This is because, firstly, it has been shown that carotid plaque is less likely to be found in the first two years after RT [4]; secondly, in the present study, carotid plaque was found in 60 % of patients with a post-RT duration of 4 years (3 out of 5 patients), which was consistent with the finding of a previous study in which 42.5 months was suggested as the cut-off value for post-RT duration for the presence of carotid plaque (around 3.5 years, a sensitivity of 68.4 % and a specificity of 50 %) [33]. When carotid plaque is found, the degree of carotid stenosis and the stability of carotid plaque can be assessed, and appropriate and prompt medications can be given to these patients to alleviate the progression of carotid atherosclerosis, which may reduce the risk of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, if patients do not have carotid plaque, the screening for carotid plaque may be performed in the fourth year after RT. This is because, firstly, it has been shown that carotid plaque is less likely to be found in the first two years after RT [4]; secondly, in the present study, carotid plaque was found in 60 % of patients with a post-RT duration of 4 years (3 out of 5 patients), which was consistent with the finding of a previous study in which 42.5 months was suggested as the cut-off value for post-RT duration for the presence of carotid plaque (around 3.5 years, a sensitivity of 68.4 % and a specificity of 50 %) [33]. When carotid plaque is found, the degree of carotid stenosis and the stability of carotid plaque can be assessed, and appropriate and prompt medications can be given to these patients to alleviate the progression of carotid atherosclerosis, which may reduce the risk of stroke.…”
Section: Discussionsupporting
confidence: 93%
“…Although different predictors of carotid intima-media thickness (CIMT) and carotid stenosis in patients treated with neck RT have been reported in previous studies [7] , [8] , no previous studies have investigated the cumulative effect of conventional cardiovascular risk factors, such as diabetes mellitus, hypertension, hyperlipidemia and smoking, on radiation-induced carotid atherosclerosis in post-RT NPC patients. In addition, significant carotid stenosis (≥50% stenosis) is an important indicator of carotid atherosclerosis and is useful for predicting cerebrovascular events [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there were only 8 patients (8/96, 8%) with moderate ICA stenosis (30-69%) and none with common carotid artery (CCA) or ICA stenosis of ≥70% or occlusion. Similarly, Huang et al [4] showed that the intima-media thickness (IMT) of the CCA was significantly increased in nasopharyngeal carcinoma patients after RT compared to the control group. They also found that the IMT, a good indicator of the severity of atherosclerotic disease, increased in a linear manner with duration of RT.…”
Section: Incidence and Prevalence Of Rt-induced Carotid Stenosismentioning
confidence: 99%
“…In addition, the IMT increased linearly with duration of RT [4]. Furthermore, elderly patients with increased CIMT and without a history of cardiovascular disease are directly associated with a remarkably higher risk of myocardial infarction and stroke [33] .…”
Section: Diagnosismentioning
confidence: 99%